In vitro cholesterol-lowering activity of probiotics isolated from commercial products in Medan City - Komala, William; Fachrial, Edy; Lister, Clarissa (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
Regular consumption of probiotic drinks has been shown to provide numerous benefits for human health. One of the primary benefits is boosting the immune system by promoting optimal digestive health. Ten brands of probiotic milk were collected, and bacterial isolates were obtained through a series of isolation and purification steps. The characterization of these isolates involved morphological and biochemical tests, including Gram staining, catalase activity assessment, and tolerance testing under simulated gastric conditions. The cholesterol-lowering activity of the isolates was evaluated in vitro by assessing their ability to reduce cholesterol levels in a simulated intestinal environment. The results demonstrated the presence of potential probiotic strains with cholesterol-lowering activity, providing a foundation for further research into the development of functional dairy products with cholesterol-lowering properties. The results indicated that probiotic milk from commercial beverages demonstrated a favorable response to bile salts in individuals with high cholesterol levels. Probiotic bacteria, such as Lactobacillus acidophilus, can survive in bile, facilitating the deconjugation of bile salts. This suggests that regular consumption of probiotic milk may aid in managing cholesterol levels in individuals with unhealthy lipid profiles. A significant relationship exists between the tolerance of probiotic milk to the digestive environment and its effectiveness in managing cholesterol. Mechanisms including bile salt deconjugation, short-chain fatty acid (SCFA) production, and increased cholesterol excretion contribute to cholesterol management. With appropriate formulation, probiotic milk can effectively control cholesterol levels, particularly in individuals at risk for cardiovascular disease.